Cytoskeletal proteins in cortical development and disease: actin associated proteins in periventricular heterotopia - Lian, Gewei; Sheen, Volney L. (Frontiers in Cellular Neuroscience, 2015)
The actin cytoskeleton regulates many important cellular processes in the brain, including cell division and proliferation, migration, and cytokinesis and differentiation. These developmental processes can be regulated through actin dependent vesicle and organelle movement, cell signaling, and the establishment and maintenance of cell junctions and cell shape. Many of these processes are mediated by extensive and intimate interactions of actin with cellular membranes and proteins. Disruption in the actin cytoskeleton in the brain gives rise to periventricular heterotopia (PH), a malformation of cortical development, characterized by abnormal neurons clustered deep in the brain along the lateral ventricles. This disorder can give rise to seizures, dyslexia and psychiatric disturbances. Anatomically, PH is characterized by a smaller brain (impaired proliferation), heterotopia (impaired initial migration) and disruption along the neuroependymal lining (impaired cell-cell adhesion). Genes causal for PH have also been implicated in actin-dependent processes. The current review provides mechanistic insight into actin cytoskeletal regulation of cortical development in the context of this malformation of cortical development.